Acute herpes hepatitis in pregnancy. - Fink, C G (1993)
A 36 year old primigravid woman presented with a "flu-like" illness and premature labour, followed by severe pneumonitis and hepatitis in the late second trimester of pregnancy. Progressive deterioration obliged an elective delivery of twins, stillborn at 25 weeks of gestation. Herpes virus isolated from one placenta, but not from any fetal tissue, was the only indication of a systemic herpes simplex infection in which there were no mucocutaneous lesions seen before or during the illness. There was no history of herpes simplex infection and antibody studies were not helpful initially for a diagnosis that was confirmed in retrospect. Double staining for viral DNA and antigen showed that the virus was present in host monocytes.